EFEKTIVITAS GURU DALAM PELAKSANAAN PENDIDIKAN ISLAM MULTIKULTURAL - Adrian Maulana; Khusnul Wardan (Almarhalah: Jurnal Pendidikan Islam, 2025)
This study examines teacher effectiveness in implementing multicultural Islamic education in a pluralistic society. The research aims to understand how teachers design, execute, evaluate, and exemplify inclusive learning that fosters tolerance, justice, and respect for diversity. Using a qualitative library research approach, relevant literature was analyzed to explore strategies that promote student engagement, collaboration, and social-emotional growth. The findings reveal that effective teachers integrate multicultural values into lesson planning, apply dialogical and participatory teaching methods, and design assessments that measure not only cognitive achievement but also attitudes and social behaviors. Exemplary behavior plays a central role, as students model their conduct on teachers’ daily actions, reinforcing ethical and moral standards. Despite challenges such as limited training, insufficient teaching materials, and social resistance, opportunities exist through supportive educational policies, digital learning tools, and professional development initiatives. Effective teachers transform these challenges into opportunities for innovation, ensuring that multicultural Islamic education cultivates empathy, inclusivity, and moderation among learners. The study concludes that teacher effectiveness encompasses strategic planning, active implementation, comprehensive evaluation, and moral exemplarity, contributing to the formation of students capable of thriving in diverse and harmonious communities.